Prevalence and Pattern of Traumatic Dental Injury Among Patients Visiting a Tertiary Care Center: A Cross-Sectional Study - Singh, Harendra Mohan; Hussain, Md. Asdaq; Singh, Abanish; Shah, Rajesh; Sah, Harish Kumar; Kumar, Abhay (Med Phoenix, 2024)
Introduction: Dental trauma is a common dental public health problem worldwide. It has a physical as well as a psychological effect. Despite this concern, data regarding its prevalence is insufficient in the literature of Nepal and specifically for this particular region of Nepal. Hence, the aim of this study is to investigate the prevalence and pattern of traumatic dental injuries for the patients visiting the Dental campus of National Medical College, Birgunj, Nepal. Materials and Methods: A cross-sectional study was conducted and ethical clearance was taken from institutional review committee of National Medical College. After obtaining the written consent from patient or guardian; history was taken and clinical examination was done under dental operating light. The following information was collected for each patient's gender, age at the time of injury, Day and month of trauma, cause of injury, and type of dental injury. Qualitative data was presented as frequencies and percentages. Results: Out of 400 patients registered during the study period, 59 patients (14.8%) were due to traumatic dental injury. Most frequently, injuries occurred in June (33.9%). Road traffic accidents (32.2 %) were the most common mode, and complicated crown-root fracture (22%) was the most common type of traumatic dental injury. Conclusion: The prevalence of 14.8 % of traumatic dental injury indicates that dental trauma needs special attention. Policy and guidelines need to be formulated and implemented by the responsible authorities to prevent and manage it.